NCERT Solutions For Class 11 Maths Chapter 11 Exercise 11.1

Go back to  'Conic Sections'

Chapter 11 Ex.11.1 Question 1

Find the equation of the circle with centre \(\left( {0,\;2} \right)\) and radius \(2.\)

Solution

The equation of a circle with centre\(\left( {h,\;k} \right)\) and radius \(r\) is given as

\[{\left( {x - h} \right)^2} + {\left( {y - k} \right)^2} = {r^2}\]

It is given that centre \(\left( {h,\;k} \right) = \left( {0,\;2} \right)\) and radius \(\left( r \right) = 2\).

Therefore, the equation of the circle is

\[\begin{align}{\left(x - 0 \right)^2} + {\left( y - 2 \right)^2} &= {2^2}\\{x^2} + {y^2} - 4y + 4 &= 4\\{x^2} + {y^2} - 4y &= 0\end{align}\]

Chapter 11 Ex.11.1 Question 2

Find the equation of the circle with centre \(\left( { - 2,\;3} \right)\) and radius \(4.\)

Solution

The equation of a circle with centre \(\left( {h,\;k} \right)\) and radius \(r\) is given as

\[{\left( {x - h} \right)^2} + {\left( {y - k} \right)^2} = {r^2}\]

It is given that centre \(\left( {h,\;k} \right) = \left( { - 2,\;3} \right)\)and radius \(\left( r \right) = 4\).

Therefore, the equation of the circle is

\[\begin{align}{\left( {x + 2} \right)^2} + {\left( {y - 3} \right)^2} &= {4^2}\\{x^2} + 4x + 4 + {y^2} - 6y + 9 &= 16\\{x^2} + {y^2} + 4x - 6y - 3 &= 0\end{align}\]

Chapter 11 Ex.11.1 Question 3

Find the equation of the circle with centre \(\left( {\frac{1}{2},\;\frac{1}{4}} \right)\) and radius \(\left( {\frac{1}{{12}}} \right)\)

Solution

The equation of a circle with centre \(\left( {h,\;k} \right)\) and radius \(r\) is given as

\[{\left( {x - h} \right)^2} + {\left( {y - k} \right)^2} = {r^2}\]

It is given that centre \(\left( {h,\;k} \right) = \left( {\frac{1}{2},\;\frac{1}{4}} \right)\) and radius \(\left( r \right) = \frac{1}{{12}}\).

Therefore, the equation of the circle is

\[\begin{align}{\left( {x - \frac{1}{2}} \right)^2} + {\left( {y - \frac{1}{4}} \right)^2} &= {\left( {\frac{1}{{12}}} \right)^2}\\{x^2} - x + \frac{1}{4} + {y^2} - \frac{y}{2} + \frac{1}{{16}} & = \frac{1}{{144}}\\{x^2} - x + \frac{1}{4} + {y^2} - \frac{y}{2} + \frac{1}{{16}} - \frac{1}{{144}} &= 0\\144{x^2} - 144x + 36 + 144{y^2} - 72y + 9 - 1 &= 0\\144{x^2} - 144x + 144{y^2} - 72y + 44 &= 0\\36{x^2} - 36x + 36{y^2} - 18y + 11 &= 0\\36{x^2} + 36{y^2} - 36x - 18y + 11 &= 0\end{align}\]

Chapter 11 Ex.11.1 Question 4

Find the equation of the circle with centre \(\left( {1,\;1} \right)\) and radius \(\sqrt 2 \)

Solution

The equation of a circle with centre \(\left( {h,\;k} \right)\) and radius \(r\) is given as

\[{\left( {x - h} \right)^2} + {\left( {y - k} \right)^2} = {r^2}\]

It is given that centre \(\left( {h,\;k} \right) = \left( {1,\;1} \right)\)and radius \(\left( r \right) = \sqrt 2 \).

Therefore, the equation of the circle is

\[\begin{align}{\left( {x - 1} \right)^2} + {\left( {y - 1} \right)^2} &= {\left( {\sqrt 2 } \right)^2}\\{x^2} - 2x + 1 + {y^2} - 2y + 1 &= 2\\{x^2} + {y^2} - 2x - 2y &= 0\end{align}\]

Chapter 11 Ex.11.1 Question 5

Find the equation of the circle with centre \(\left( { - a,\; - b} \right)\) and radius \(\sqrt {{a^2} - {b^2}} \)

Solution

The equation of a circle with centre \(\left( {h,\;k} \right)\) and radius \(r\) is given as

\[{\left( {x - h} \right)^2} + {\left( {y - k} \right)^2} = {r^2}\]

It is given that centre\(\left( {h,\;k} \right) = \left( { - a,\; - b} \right)\)and radius\(\left( r \right) = \sqrt {{a^2} - {b^2}} \)

Therefore, the equation of the circle is

\[\begin{align}{\left( {x + a} \right)^2} + {\left( {y + b} \right)^2} &= {\left( {\sqrt {{a^2} - {b^2}} } \right)^2}\\{x^2} + 2ax + {a^2} + {y^2} + 2by + {b^2} &= {a^2} - {b^2}\\{x^2} + {y^2} + 2ax + 2by + 2{b^2} &= 0\end{align}\]

Chapter 11 Ex.11.1 Question 6

Find the centre and radius of the circle \({\left( {x + 5} \right)^2} + {\left( {y - 3} \right)^2} = 36\)

Solution

The equation of the given circle is \({\left( {x + 5} \right)^2} + {\left( {y - 3} \right)^2} = 36\)

\[\begin{align}&\Rightarrow\; {\left( {x + 5} \right)^2} + {\left( {y - 3} \right)^2} = 36\\&\Rightarrow\; {\left[ {x - \left( { - 5} \right)} \right]^2} + {\left( {y - 3} \right)^2} = {6^2}\end{align}\]

which is of the form \({\left( {x - h} \right)^2} + {\left( {y - k} \right)^2} = {r^2}\)

Therefore, on comparing both equations we get

\(h = - 5,\;k = 3\) and \(r=6\)

Thus, the centre of the given circle is while its radius is \(6.\)

Chapter 11 Ex.11.1 Question 7

Find the centre and radius of the circle \({x^2} + {y^2} - 4x - 8y - 45 = 0\)

Solution

The equation of the given circle is \({x^2} + {y^2} - 4x - 8y - 45 = 0\).

\[\begin{align}&\Rightarrow \;{x^2} + {y^2} - 4x - 8y - 45 = 0\\&\Rightarrow \;\left( {{x^2} - 4x} \right) + \left( {{y^2} - 8y} \right) = 45\\&\Rightarrow \;\left\{ {{x^2} - 2\left( x \right)\left( 2 \right) + {2^2}} \right\} + \left\{ {{y^2} - 2\left( y \right)\left( 4 \right) + {4^2}} \right\}\\&\quad- 4 - 16 = 45\\&\Rightarrow \;{\left( {x - 2} \right)^2} + {\left( {y - 4} \right)^2} = 65\\&\Rightarrow \;{\left( {x - 2} \right)^2} + {\left( {y - 4} \right)^2} = {\left( {\sqrt {65} } \right)^2}\end{align}\]

which is of the form \({\left( {x - h} \right)^2} + {\left( {y - k} \right)^2} = {r^2}\)

Therefore, on comparing both equations we get

\(h = 2,\;k = 4\) and \(r = \sqrt {65} \)\(\sqrt {65} \)

Thus, the centre of the given circle is \(\left( {2,4} \right)\) while its radius is \(\sqrt {65} \).

Chapter 11 Ex.11.1 Question 8

Find the centre and radius of the circle \({x^2} + {y^2} - 8x + 10y - 12 = 0\)

Solution

The equation of the given circle is \({x^2} + {y^2} - 8x + 10y - 12 = 0\).

\[\begin{align}&\Rightarrow \;{x^2} + {y^2} - 8x + 10y - 12 = 0\\&\Rightarrow \; \left( {{x^2} - 8x} \right) + \left( {{y^2} + 10y} \right) = 12\\&\Rightarrow \; \left\{ {{x^2} - 2\left( x \right)\left( 4 \right) + {4^2}} \right\} + \left\{ {{y^2} + 2\left( y \right)\left( 5 \right) + {5^2}} \right\} \\&\quad- 16 - 25 = 12\\&\Rightarrow \;{\left( {x - 4} \right)^2} + {\left( {y + 5} \right)^2} = 53\\&\Rightarrow \;{\left( {x - 4} \right)^2} + {\left[ {y - \left( { - 5} \right)} \right]^2} = {\left( {\sqrt {53} } \right)^2}\end{align}\]

which is of the form \({\left( {x - h} \right)^2} + {\left( {y - k} \right)^2} = {r^2}\)

Therefore, on comparing both equations we get

\(h = 4,\;k = - 5\) and \(r = \sqrt {53} \)

Thus, the centre of the given circle is \(\left( {4, - 5} \right)\) while its radius is \(\sqrt {53} \).

Chapter 11 Ex.11.1 Question 9

Find the centre and radius of the circle \(2{x^2} + 2{y^2} - x = 0\)

Solution

The equation of the given circle is \(2{x^2} + 2{y^2} - x = 0\)

\[\begin{align}&\Rightarrow \;2{x^2} + 2{y^2} - x = 0\\&\Rightarrow \;\left( {2{x^2} - x} \right) + 2{y^2} = 0\\&\Rightarrow \;2\left[ {\left( {{x^2} - \frac{x}{2}} \right) + {y^2}} \right] = 0\\&\Rightarrow \;\left\{ {{x^2} - 2\left( x \right)\left( {\frac{1}{4}} \right) + {{\left( {\frac{1}{4}} \right)}^2}} \right\} + {y^2} - {\left( {\frac{1}{4}} \right)^2} = 0\\&\Rightarrow \;{\left( {x - \frac{1}{4}} \right)^2} + {\left( {y - 0} \right)^2} = {\left( {\frac{1}{4}} \right)^2}\end{align}\]

which is of the form \({\left( {x - h} \right)^2} + {\left( {y - k} \right)^2} = {r^2}\)

Therefore, on comparing both equations we get

\(h = \frac{1}{4},\;k = 0\) and \(r = \frac{1}{4}\)

Thus, the centre of the given circle is \(\left( {\frac{1}{4},0} \right)\) while its radius is \(\frac{1}{4}\).

Chapter 11 Ex.11.1 Question 10

Find the equation of the circle passing through the points \(\left( 4,1 \right)\) and \(\left( {6,5} \right)\) and whose centre is on the line \(4x + y = 16\).

Solution

Let the equation of the required circle be \({\left( {x - h} \right)^2} + {\left( {y - k} \right)^2} = {r^2}\).

Since the circle passes through the points \(\left( {4,1} \right)\) and \(\left( {6,5} \right)\)

\[\begin{align}{\left( {4 - h} \right)^2} + {\left( {1 - k} \right)^2} &= {r^2} \qquad \ldots \left( 1 \right)\\{\left( {6 - h} \right)^2} + {\left( {5 - k} \right)^2} &= {r^2} \qquad \ldots \left( 2 \right)\end{align}\]

Since the centre \(\left( {h,\;k} \right)\) of the circle lies on the line \(4x + y = 16\)

\[4h + k = 16 \quad \ldots \left( 3 \right)\]

From equations \(\left( 1 \right)\) and \(\left( 2 \right)\), we obtain

\[\begin{align}&\Rightarrow \;{\left( {4 - h} \right)^2} + {\left( {1 - k} \right)^2} = {\left( {6 - h} \right)^2} + {\left( {5 - k} \right)^2}\\&\Rightarrow \;16 - 8h + {h^2} + 1 - 2k + {k^2} = 36 - 12h + {h^2} + 25 - 10k + {k^2}\\&\Rightarrow \;16 - 8h + 1 - 2k = 36 - 12h + 25 - 10k\\&\Rightarrow \;4h + 8k = 44\\&\Rightarrow\; h + 2k = 11 \qquad \qquad \ldots \left( 4 \right)\end{align}\]

On solving equations \(\left( 3 \right)\) and \(\left( 4 \right)\), we obtain

\(h = 3\) and \(k = 4\)

On substituting the values of \(h\) and \(k\) in equation \(\left( 1 \right)\), we obtain

\[\begin{align}&{\left( {4 - 3} \right)^2} + {\left( {1 - 4} \right)^2} = {r^2}\\&\Rightarrow\; {1^2} + {\left( { - 3} \right)^2} = {r^2}\\&\Rightarrow \;1 + 9 = {r^2}\\&\Rightarrow \;{r^2} = 10\\&\Rightarrow \;r = \sqrt {10}\end{align}\]

Thus, the equation of the required circle is

\[\begin{align}{\left( {x - 3} \right)^2} + {\left( {y - 4} \right)^2} &= {\left( {\sqrt {10} } \right)^2}\\{x^2} - 6x + 9 + {y^2} - 8y + 16 &= 10\\{x^2} + {y^2} - 6x - 8y + 15& = 0\end{align}\]

Chapter 11 Ex.11.1 Question 11

Find the equation of the circle passing through the points \(\left( {2,3} \right)\) and \(\left( { - 1,1} \right)\) and whose centre is on the line \(x - 3y - 11 = 0\).

Solution

Let the equation of the required circle be \({\left( {x - h} \right)^2} + {\left( {y - k} \right)^2} = {r^2}\).

Since the circle passes through the points \(\left( {2,3} \right)\) and \(\left( { - 1,1} \right)\)

\[\begin{align}{\left( {2 - h} \right)^2} + {\left( {3 - k} \right)^2} = {r^2} \qquad \ldots \left( 1 \right)\\{\left( { - 1 - h} \right)^2} + {\left( {1 - k} \right)^2} = {r^2} \qquad \ldots \left( 2 \right)\end{align}\]

Since the centre \(\left( {h,\;k} \right)\) of the circle passes lies on the line \(x - 3y - 11 = 0\),

\[h - 3k = 11 \qquad \ldots \left( 3 \right)\]

From equations \(\left( 1 \right)\) and \(\left( 2 \right)\), we obtain

\[\begin{align}&{\left( {2 - h} \right)^2} + {\left( {3 - k} \right)^2} = {\left( { - 1 - h} \right)^2} + {\left( {1 - k} \right)^2}\\&\Rightarrow \;4 - 4h + {h^2} + 9 - 6k + {k^2} = 1 + 2h + {h^2} + 1 + {k^2} - 2k\\&\Rightarrow\; 4 - 4h + 9 - 6k = 1 + 2h + 1 - 2k\\&\Rightarrow \;6h + 4k = 11 \qquad \qquad  \ldots \left( 4 \right)\end{align}\]

On solving equations \(\left( 3 \right)\) and \(\left( 4 \right)\), we obtain

\(h = \frac{7}{2}\) and \(k = \frac{{ - 5}}{2}\)

On substituting the values of \(h\) and \(k\) in equation \(\left( 1 \right)\), we obtain

\[\begin{align}&\Rightarrow\; {\left( {2 - \frac{7}{2}} \right)^2} + {\left( {3 + \frac{5}{2}} \right)^2} = {r^2}\\&\Rightarrow\; {\left( {\frac{{4 - 7}}{2}} \right)^2} + {\left( {\frac{{6 + 5}}{2}} \right)^2} = {r^2}\\&\Rightarrow\; {\left( {\frac{{ - 3}}{2}} \right)^2} + {\left( {\frac{{11}}{2}} \right)^2} = {r^2}\\&\Rightarrow\; \frac{9}{4} + \frac{{121}}{4} = {r^2}\\&\Rightarrow\; \frac{{130}}{4} = {r^2}\end{align}\]

Thus, the equation of the required circle is

\[\begin{align}{\left( {x - \frac{7}{2}} \right)^2} + {\left( {y + \frac{5}{2}} \right)^2} &= \frac{{130}}{4}\\{\left( {\frac{{2x - 7}}{2}} \right)^2} + {\left( {\frac{{2y + 5}}{2}} \right)^2} &= \frac{{130}}{4}\\4{x^2} - 28x + 49 + 4{y^2} + 20y + 25 &= 130\\4{x^2} + 4{y^2} - 28x + 20y - 56 &= 0\\4\left( {{x^2} + {y^2} - 7x + 5y - 14} \right) &= 0\\{x^2} + {y^2} - 7x + 5y - 14 &= 0\end{align}\]

Chapter 11 Ex.11.1 Question 12

Find the equation of the circle with radius \(5\) whose centre lies on \(x\)-axis and passes through the point \(\left( {2,\;3} \right)\).

Solution

Let the equation of the required circle be \({\left( {x - h} \right)^2} + {\left( {y - k} \right)^2} = {r^2}\).

Since the radius of the circle is \(5\) and its centre lies on the \(x\)-axis, \(k = 0\) and \(r = 5\).

Now, the equation of the circle becomes\({\left( {x - h} \right)^2} + {y^2} = 25\).

It is given that the circle passes through the point \(\left( {2,3} \right)\).

Therefore,

\[\begin{align}&\Rightarrow\; {\left( {2 - h} \right)^2} + {3^2} = 25\\&\Rightarrow \;{\left( {2 - h} \right)^2} = 25 - 9\\&\Rightarrow \;{\left( {2 - h} \right)^2} = 16\\&\Rightarrow \;2 - h = \pm \sqrt {16} \\&\Rightarrow\; 2 - h = \pm 4\end{align}\]

If, \(2 - h = 4\), then \(h = - 2\)

If \(2 - h = - 4\), then \(h = 6\)

When \(h = - 2\), the equation of the circle becomes

\[\begin{align}{\left( {x + 2} \right)^2} + {y^2} &= 25\\{x^2} + 4x + 4 + {y^2} &= 25\\{x^2} + {y^2} + 4x - 21 &= 0\end{align}\]

When \(h = 6\), the equation of the circle becomes

\[\begin{align}{\left( {x - 6} \right)^2} + {y^2} &= 25\\{x^2} - 12x + 36 + {y^2} &= 25\\{x^2} + {y^2} - 12x + 11 & = 0\end{align}\]

Chapter 11 Ex.11.1 Question 13

Find the equation of the circle passing through \(\left( {0,0} \right)\) and making intercepts \(a\) and \(b\) on the coordinate axes.

Solution

Let the equation of the required circle be \({\left( {x - h} \right)^2} + {\left( {y - k} \right)^2} = {r^2}\).

Since the circle passes through \(\left( {0,0} \right)\),

\[\begin{align}&{\left( {0 - h} \right)^2} + {\left( {0 - k} \right)^2} = {r^2}\\&\Rightarrow\; {h^2} + {k^2} = {r^2}\end{align}\]

The equation of the circle now becomes \({\left( {x - h} \right)^2} + {\left( {y - k} \right)^2} = {h^2} + {k^2}\).

It is given that the circle makes intercepts \(a\) and \(b\) on the coordinate axes. This means that the circle passes through points \(\left( {a,0} \right)\) and \(\left( {0,b} \right)\).

Therefore,

\[\begin{align}{\left( {a - h} \right)^2} + {\left( {0 - k} \right)^2} &= {h^2} + {k^2} \qquad \ldots \left( 1 \right)\\{\left( {0 - h} \right)^2} + {\left( {b - k} \right)^2} &= {h^2} + {k^2} \qquad \ldots \left( 2 \right)\end{align}\]

From equation \(\left( 1 \right)\), we obtain

\[\begin{align}&\Rightarrow \;{a^2} + {h^2} - 2ah + {k^2} = {h^2} + {k^2}\\&\Rightarrow \;{a^2} - 2ah = 0\\&\Rightarrow \;a\left( {a - 2h} \right) = 0\\&\Rightarrow\; a = 0{\text{ or }}\left( {a - 2h} \right) = 0\end{align}\]

However, \(a \ne 0\);

Hence,

\[\begin{align}&\left( {a - 2h} \right) = 0\\&\Rightarrow\;h = \frac{a}{2}\end{align}\]

From equation \(\left( 2 \right)\), we obtain

\[\begin{align}&{h^2} + {b^2} - 2bk + {k^2} = {h^2} + {k^2}\\&\Rightarrow \;{b^2} - 2bk = 0\\&\Rightarrow \;b\left( {b - 2k} \right) = 0\\&\Rightarrow \; b = 0\;{\rm{or}}\;\left( {b - 2k} \right) = 0\end{align}\]

However, \(b \ne 0\);

Hence,

\[\begin{align}&\left( {b - 2k} \right) = 0\\&\Rightarrow \; k = \frac{b}{2}\end{align}\]

Thus, the equation of the required circle is

\[\begin{align}&\Rightarrow\; {\left( {x - \frac{a}{2}} \right)^2} + {\left( {y - \frac{b}{2}} \right)^2} = {\left( {\frac{a}{2}} \right)^2} + {\left( {\frac{b}{2}} \right)^2}\\&\Rightarrow \;{\left( {\frac{{2x - a}}{2}} \right)^2} + {\left( {\frac{{2y - b}}{2}} \right)^2} = \frac{{{a^2} + {b^2}}}{4}\\&\Rightarrow\; 4{x^2} - 4ax + {a^2} + 4{y^2} - 4by + {b^2} = {a^2} + {b^2}\\&\Rightarrow \;4{x^2} + 4{y^2} - 4ax - 4by = 0\\&\Rightarrow \;4\left( {{x^2} + {y^2} - ax - by} \right) = 0\\&\Rightarrow \;{x^2} + {y^2} - ax - by = 0\end{align}\]

Chapter 11 Ex.11.1 Question 14

Find the equation of a circle with centre \(\left( {2,2} \right)\) and passes through the point \(\left( {4,5} \right)\).

Solution

The centre of the circle is given as \(\left( {h,k} \right) = \left( {2,2} \right)\)

Since the circle passes through the point \(\left( {4,5} \right)\), the radius \(\left( r \right)\) of the circle is the distance between the points \(\left( {2,2} \right)\)and \(\left( {4,5} \right)\).

Therefore,

\[\begin{align}r &= \sqrt {{{\left( {2 - 4} \right)}^2} + {{\left( {2 - 5} \right)}^2}} \\&= \sqrt {{{\left( { - 2} \right)}^2} + {{\left( { - 3} \right)}^2}} \\&= \sqrt {4 + 9} \\&= \sqrt {13}\end{align}\]

Thus, the equation of the circle is

\[\begin{align}&{\left( {x - h} \right)^2} + {\left( {y - k} \right)^2} = {r^2}\\&{\left( {x - 2} \right)^2} + {\left( {y - 2} \right)^2} = {\left( {\sqrt {13} } \right)^2}\\&{x^2} - 4x + 4 + {y^2} - 4y + 4 = 13\\&{x^2} + {y^2} - 4x - 4y - 5 = 0\end{align}\]

Chapter 11 Ex.11.1 Question 15

Does the point \(\left( { - 2.5,\;3.5} \right)\) lie inside, outside or on the circle \({x^2} + {y^2} = 25\)?

Solution

The equation of the given circle is \({x^2} + {y^2} = 25\)

\[\begin{align}&\Rightarrow \;{x^2} + {y^2} = 25\\&\Rightarrow \;{\left( {x - 0} \right)^2} + {\left( {y - 0} \right)^2} = {5^2}\end{align}\]

which is of the form \({\left( {x - h} \right)^2} + {\left( {y - k} \right)^2} = {r^2}\), where \(h = 0,\;k = 0\) and \(r = 5\)

Therefore, Centre\( \Rightarrow \left( {0,0} \right)\) and radius \( \Rightarrow 5\)

Distance between point \(\left( { - 2.5,\;3.5} \right)\) and centre \(\left( {0,0} \right)\)

\[\begin{align}&= \sqrt {{{\left( { - 2.5 - 0} \right)}^2} + {{\left( {3.5 - 0} \right)}^2}} \\&= \sqrt {6.25 + 12.25} \\&= \sqrt {18.25} \\&= 4.272\end{align}\]

Here, \(4.272 < 5\), this means less than the radius.

Since the distance between the point \(\left( { - 2.5,\;3.5} \right)\) and centre \(\left( {0,0} \right)\) of the circle is less than the radius of the circle, hence, the point \(\left( { - 2.5,\;3.5} \right)\) lies inside the circle.

  
Download Cuemath NCERT App
Related Sections
Related Sections

Learn from the best math teachers and top your exams

Learn from the best

math teachers and top

your exams


Personalized Curriculum
Instant Doubts clarification
Cover latest CBSE Syllabus
Unlimited Mock & Practice tests
Covers CBSE, ICSE, IB curriculum

Instant doubt clearing with Cuemath Advanced Math Program
0